Patient engagement pilot for uncontrolled hypertension: implications for quality, safety, and population health - Molly L. Daughtry; Kristen E. Miller; Kristen E. Miller; David Brennan; Joseph B. Brodine; Joseph B. Brodine (Frontiers in Health Services)
IntroductionTraditional methods of hypertension management often fall short in ensuring timely intervention and sustained patient engagement. This study explores the implementation of a patient-generated health data (PGHD) system using a text-message based platform to enhance patient engagement and improve hypertension control across diverse populations.MethodsWe conducted a patient engagement campaign at MedStar Health within the Maryland Primary Care Program (MDPCP), targeting patients with poorly controlled hypertension across 54 clinics. The intervention utilized the Twistle platform to send automated text messages to patients, encouraging them to submit their home blood pressure readings. Data collection was automated, and the intervention's effectiveness was assessed through engagement metrics and blood pressure control outcomes.ResultsOver a 20-day period, 11,597 patients were targeted, with 9,216 successfully receiving and engaging with the intervention. Of these, 28.5% responded with a blood pressure reading. Follow-up adjustments in patient care plans were made based on 1,209 responses indicating improved control of hypertension. The initiative demonstrated significant improvement in patient engagement and quality of hypertension management.DiscussionThe use of PGHD via text messaging significantly enhanced patient engagement and the management of hypertension, contributing to better quality outcomes and patient safety. This approach proved particularly effective in reaching and impacting patients in underserved communities, where traditional healthcare interactions are often limited. The findings support broader adoption of PGHD interventions in chronic disease management and underscore the potential for digital health tools to transform patient care by actively involving patients in their health management.